2017
DOI: 10.5897/ajb2016.15823
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals bioremediation potential of Klebsiella species isolated from diesel polluted soil

Abstract: Heavy metals are transition elements whose presence at mild doses in water bodies is deadly. Most effectively harnessed technique of their remediation is, respectively. It can be concluded that the trend of each microbe's and the consortium's affinity for the heavy metals uptake is predictably in the trend Cr > Cd > Cu > Ni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…This strain is usually isolated from hydrocarbon-contaminated areas and tolerates high concentrations of heavy metals and hydrocarbons. Moreover, it is also an important part of the microbial community that is involved in petroleum biodegradation processes (Aransiola et al 2017;Rodrigues et al 2009). In this manner, the clinical and environmental Kp1 and Kp2 strains were investigated in terms of their petroleum degradation abilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain is usually isolated from hydrocarbon-contaminated areas and tolerates high concentrations of heavy metals and hydrocarbons. Moreover, it is also an important part of the microbial community that is involved in petroleum biodegradation processes (Aransiola et al 2017;Rodrigues et al 2009). In this manner, the clinical and environmental Kp1 and Kp2 strains were investigated in terms of their petroleum degradation abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Klebsiella pneumoniae, a gram-negative, coccobacilli, facultative, non-motile, usually encapsulated bacteria belonging to Enterobacteriaceae, is an important opportunistic pathogen besides its ability to live in different environments (Aransiola et al 2017;Lee et al 2013;Rajkumari et al 2018). Its ability to survive in different habitats and to degrade the organic compounds such as petroleum are related to its genetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiealla planticola grew anaerobically at a Cd dose of 15 mM and precipitated CdS (Sharma et al, 2000). Aransiola et al (2017) reported that K. edwardsii, K. oxytoca, and K. pneumoniae strains isolated from diesel polluted soil significantly reduced Cadmium, copper and nickel. Several studies have revealed that mechanism of bio-sorption were convincingly associated to physicochemical interaction of metal in solution (Aksu et al, 2002;Lodeiro et al, 2006;Amini et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiealla planticola grew anaerobically at a Cd dose of 15 mM and precipitated CdS ( Sharma et al., 2000 ). Aransiola et al (2017) reported that K. edwardsii, K . oxytoca, and K. pneumoniae strains isolated from diesel polluted soil significantly reduced Cadmium, copper and nickel.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella sp. yang diisolasi dari tanah yang tercemar bahan bakar terbukti resisten terhadap kromium, kadmium, dan tembaga (Aransiola et al, 2017). Acinetobacter sp.…”
Section: Hasil Dan Pembahasan Uji Resistensi Acinetobacter Sp Irc2 Terhadap Berbagai Logam Beratunclassified